How affective factors can influence teenager`s reluctancy to speak english in the classroom - Romero, Noemi (2011)
Education in the province of Buenos Aires can be divided into two main groups: Education in bilingual schools where students are immersed in the language from an early age, with all the necessary resources at hand, such as books, dictionaries, access to the Internet, access to a classroom with video recorders, and so on. These students have the opportunity to learn in a comfortable environment, with technology available in the classroom and the tools required to acquire knowledge. On the other hand, there is another group, which constitutes the majority of students in the suburban areas of Great Buenos Aires. This group is lacked in the basic needs such as housing and food, so those schools are currently seen as places whose main objective is to cater for those necessities. We must add that the deplorable conditions in which most of the state schools are do not provide the students with the “comfortable environment” desired for the learning process. Seen in this light not all students can have the same opportunities as regards schooling. This inequity comes even clearer when students only come to school because it is the place where they meet peers so that they do not feel alone at home. All these factors inevitably lead to students in the second group being de-motivated in the foreign language class. It is a fact that as consequence of what was pointed out before, students in poorer areas are negatively affected and this inhibits them to perform successfully in the L2 class.